The Scholarship of Integration: On the Pivotal Role of Centers of Advanced Study in the New Structure of Research-Intensive Universities in the 21st Century (CPP RPS 61/2013) - Juchacz, Piotr W. (Center for Public Policy Research Papers Series, 2013)
Let us begin our considerations quoting an opening passage from a book edited by Peter Maassen and Johan P. Olsen University Dynamics and European Integration (2007), that allows us to sketch the broader context of our article: “European universities face demands for urgent and radical reform. A standard claim is that environments are changing rapidly and that universities are not able or willing to respond adequately. It is necessary to rethink and reshape their internal order and role in society simply because European universities do not learn, adapt and reform themselves fast enough. Reform plans comprise the purposes of universities, that is, definitions of what the University is, can be and should be, criteria for quality and success, the kinds of research, education and services to be produced, and for whom” (Olsen, Maassen: 2007: 3). Similarly Marek Kwiek stresses the growing complexity of the academic enterprise in Europe and he puts in the centre of our attention six contentious areas demanding a deepened discussion during the coming decade, such as the following: 1) university funding in mass higher education systems and the role of the cost haring; 2) the role of third stream funding; 3) changing university governance modes; 4) the delinking of teaching/research activities; 5) the differentiation processes within the academic profession; 6) the question about the further expansion of higher education systems (Kwiek 2012a: 32).